Korelasi Kualitas Air Pada Pertumbuhan Larva Ikan Bawal Bintang (Trachinotus Blochi) Di Balai Benih Ikan Laut (Bbil), Pulau Tidung Kepulauan Seribu - Catur Pramono Adi; Muhamad Fauzan; Aripudin Aripudin; Maria Goreti Eny Kristiany (Universitas Mataram, 2024)
Bintang pomfret is an introduced fish from Taiwan and has quite good prospects in the Asia Pacific region with quite high prices. This Final Practical Work Activity (KPA) aims to carry out a t-test and to determine the effect of water quality on growth, the correlation coefficient (r calculation) is calculated. The water quality parameters observed included temperature, pH and salinity. The t-test results showed that t calculated (0.008) < t table (), this means there was no significant difference between the two growth patterns in length and weight. Meanwhile, the results of the correlation coefficient between water quality and growth show that there is no real influence between the water quality parameters observed on the growth of the pomfret.